Individual differences in environmental wellbeing and pro-environmental behaviors explained by self-control - Strömbäck, Camilla; Lindkvist, Emma; Västfjäll, Daniel (Frontiers in Psychology, 2023)
Climate change is an increasing problem, with more extreme weather conditions and rising temperatures. To fulfill the temperature goals of the Paris agreement a societal change is needed, a change that requires a shift of lifestyle from all of us. If we want to change our behaviors to more sustainable ones, we need to sacrifice substantial things today to improve a future, which often seems distant and abstract. People with high level of self-control have been shown to have a better ability to visualize future events, which makes self-control an interesting trait to look at in relation to pro-environmental behavior. The aim of this study was to examine how self-control correlates with environmental well-being and environmental behavior. An internet-based survey was sent to a representative Swedish sample (n = 602). The respondents were asked to fill out a newly developed scale measuring their anxiety and security regarding environmental matters (environmental wellbeing), as well as indicate how often they engage in six different pro-environmental behaviors (e.g., turning lights off when leaving the room). Additionally, data on the respondents’ gender, age, political orientation, and self-control was collected. Our results suggest a positive correlation between self-control and environmental wellbeing and a weaker, but still positive, correlation between self-control and some pro-environmental behaviors. Additionally, respondents who identified themselves as politically left had lower environmental wellbeing, while men had higher environmental wellbeing, but behaved less environmentally friendly. Thus, our results suggest that political orientation was a better predictor of sound environmental behavior than subjective self-control was.